Effective Early Treatment of AChR Antibody-Positive Myasthenia Gravis with Rituximab; the Experience from a Neuroimmunology Clinic in a Developing Country. (May 2021) - Mathew, Thomas; Thomas, Kurian; K John, Saji; Venkatesh, Shruthi; Nadig, Raghunandan; Badachi, Sagar; Souza, Delon D; Sarma, GRK; Parry, Gareth J
Background: Rituximab is reserved for treating refractory myasthenia gravis (MG) patients. Here we report our experience with rituximab in AChR antibody positive generalized MG (gMG) and impending myasthenic crisis (IMC). Methods: This retrospective, observational study, conducted at a tertiary care, neuroimmunology clinic, analyzed the data of patients with AChR antibody positive gMG, treated with rituximab between 1st January 2016 and 30th October 2018. Results: Eleven patients with AChR antibody positive gMG received rituximab. Mean age of the cohort was 50.54 ± 18.71 years with 9 males. Seven out of 11 patients received rituximab in the early stage (<2 years from onset) and had good response to treatment. Four of the 5 patients with IMC improved with rituximab alone. In the 10 patients who regularly followed up, there was a significant difference between the QMG scores at baseline and at 1, 2, 6, 12, and 18 months ( P < .0001). Conclusion: Rituximab appears to be a potentially effective early treatment option for AChR antibody positive generalized MG and impending myasthenic crisis.